x-(-2.26)=4.69

Simple and best practice solution for x-(-2.26)=4.69 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-(-2.26)=4.69 equation:


Simplifying
x + -1(-2.26) = 4.69

Multiply -1 * -2.26
x + 2.26 = 4.69

Reorder the terms:
2.26 + x = 4.69

Solving
2.26 + x = 4.69

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2.26' to each side of the equation.
2.26 + -2.26 + x = 4.69 + -2.26

Combine like terms: 2.26 + -2.26 = 0.00
0.00 + x = 4.69 + -2.26
x = 4.69 + -2.26

Combine like terms: 4.69 + -2.26 = 2.43
x = 2.43

Simplifying
x = 2.43

See similar equations:

| 0.55555555556+q=0.66666666667 | | g=-1/2(3)+1 | | 5/25x=3 | | f(x)=x^3-8x^2+5 | | x+8/5=-3 | | g=-1/2(0)+1 | | z-8=(-30) | | 5d+3(d-5)= | | (2+6i)+(3-7i)= | | -5x+40=6-3x | | x-(-20.78)=-23.49 | | g=-1/2(4)+1 | | 5x+40+5x=180 | | 15-6t/12=3/4 | | 6(2m+n-4)= | | 33.2+x+23.3+x=191.7 | | 10m-6+2m+13= | | x^2-100x+1250=0 | | f=7(0)-6 | | x+17=-14 | | (5-2i)-(3-7i)= | | -7(3n+6)=105 | | f=7(1)-6 | | 6p+4-3p= | | 11n-8-10y-7=3 | | f=7(-2)-6 | | 4=5d-16 | | -6a+5=23 | | 13.9=x/6+12.5 | | a-5/2=3a/4+a-25/6 | | v+30=84 | | 3z/2-1=-16 |

Equations solver categories